Specific temperament in patients with nevoid basal cell carcinoma syndrome. Issue 2 (4th February 2021) - Uchikawa, Hideki; Fujii, Katsunori; Shiohama, Tadashi; Nakazato, Michiko; Shimizu, Eiji; Miyashita, Toshiyuki; Shimojo, Naoki
Abstract: Background: Nevoid basal cell carcinoma syndrome (NBCCS) is a neurocutaneous disease, characterized by tumorigenesis and developmental anomalies due to aberrant sonic hedgehog (Shh) signaling. Patients with NBCCS typically appear calm and carefree, suggesting that a specific personality in these patients may be associated with an enhanced hedgehog pathway. Our study aimed to determine the personality type in these patients. Methods: We enrolled 14 mentally normal patients with genetically confirmed NBCCS (seven males and seven females; mean age = 25.2 years) and 20 controls (10 males and 10 females; mean age = 27.9 years). The patients were assessed with the Japanese version of the Temperament and Character Inventory, based on the seven‐dimensional model of temperament and character, and their clinical symptoms were evaluated. The amygdala volumes of six patients with NBCCS were measured using magnetic resonance imaging with image‐processing software. Results: Patients with NBCCS scored significantly lower on harm avoidance (0.89) than controls (1.00; P  = 0.0084). Moreover, patients with NBCCS and developmental malformations such as rib anomalies, who may have experienced Shh signaling enhancement from the prenatal period, scored significantly lower on harm avoidance (0.80 [ P  = 0.0031]). The left amygdala volume was also significantly reduced in patients with NBCCS ( P  = 0.0426). Conclusions: Patients with NBCCS who experienced increased Shh signaling from the prenatal period showed significantly lower harm avoidance related to serotonin. The left amygdala volume was significantly reduced in these patients. Our results indicate that Shh signaling may influence the human personality.